Obstructive jaundice, early satiety and xerostomia in an 82-year-old woman. Issue 7 (8th July 2022) - Bhanot, Kunal; Taheem, Muhesh; Perry, Robert; Wong, Christopher; Muehlschlegel, Charlotte; Cheent, Kuldeep
Abstract: Amyloid light-chain (AL) amyloidosis is a multisystem disease with obstructive jaundice and gastrointestinal (GI) involvement being uncommon initial presentations. Patients with AL amyloidosis seldom have jaundice and advanced GI tract involvement as their presenting symptoms. This case report describes an 82-year-old lady who presented with a 6-month history of early satiety, weight loss, xerostomia and progressive jaundice. Imaging did not suggest a biliary cause but demonstrated hepatomegaly and ascites. Oesophagogastroduodenoscopy revealed a duodenal stricture. Duodenal and liver biopsies were consistent with amyloid deposition. Multiple myeloma was confirmed to be the underlying cause. Significant cholestatic liver dysfunction and a duodenal stricture have not been previously described as simultaneous manifestations of amyloidosis. This case also highlights the difficulty in treating multiple myeloma as the cause of AL amyloidosis in the context of liver dysfunction, given that many chemotherapy agents undergo hepatic metabolism.